2004
DOI: 10.1021/ja0317067
|View full text |Cite
|
Sign up to set email alerts
|

Connecting π-Chromophores by σ-P−P Bonds:  New Type of Assemblies Exhibiting σ−π-Conjugation

Abstract: To study the ability of sigma-P-P skeleton to mediate interaction between pi-chromophores, 1,1'-biphospholes bearing phenyl or thienyl substituents at the 2,2' and 5,5'-position have been prepared and studied. These air-stable derivatives are readily available via a "one-pot" synthesis starting from diynes. Theoretical studies and UV-vis data clearly establish that the two pi-systems interact via the sigma-P-P bridge. This through-bond interaction results in a lowering of the optical HOMO-LUMO gap of the assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 43 publications
(27 reference statements)
6
68
3
Order By: Relevance
“…GoPI Synthesis-The synthesis of [1-phenyl-2,5-di(2-pyridyl)-phosphole}AuCl] was carried out in analogy to the synthesis of [{1-phenyl-2,5-di(2-thienyl)phosphole}AuCl] (18,19) and [{1-phenyl-2,5-di(2-pyridyl)phosphole}W(CO) 5 ] (20). The reactant 1-phenyl-2,5-di(2-pyridyl)phosphole was synthesized as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…GoPI Synthesis-The synthesis of [1-phenyl-2,5-di(2-pyridyl)-phosphole}AuCl] was carried out in analogy to the synthesis of [{1-phenyl-2,5-di(2-thienyl)phosphole}AuCl] (18,19) and [{1-phenyl-2,5-di(2-pyridyl)phosphole}W(CO) 5 ] (20). The reactant 1-phenyl-2,5-di(2-pyridyl)phosphole was synthesized as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the phosphole system exhibits a peculiar electronic structure, with a low-lying LUMO energy level that is particularly attractive for organic electronics. [13] RØau and co-workers were among the first to incorporate the phosphole moiety in extended p-conjugated materials [14] and to utilize these in phosphole-based OLED devices. [15] A few years ago, we introduced the dithieno[3,2-b:2',3'-d]phos-A C H T U N G T R E N N U N G phole system (1, Scheme 1) to this field of research.…”
Section: Introductionmentioning
confidence: 99%
“…While the spectrum of (3a) shows only one absorption due to a p-p* transition (412 nm), several bands are recorded for (12) with one red shifted broad shoulder (k onset = 560 nm) (Fig. 2) [20]. The TD-DFT simulated absorptions of (12) (vertical lines, Fig.…”
Section: Co-oligomers Containing Phosphole Ringsmentioning
confidence: 96%
“…We anticipated that P-P bridges could be potentially good candidates to mediate through-bond conjugation since they possess a low rr* gap. Compound (12) (Scheme 4) [20], assembling two di(2-thienyl)phosphole chromophores via a P-P bond, was prepared according to the classical route to 1,1 0 -biphospholes, implying a coupling of the corresponding phospholyl anion upon oxidation with iodine [21]. An X-ray diffraction study performed on (12) revealed a P-P single bond [2.224(1) Å ] [22] and showed that the P atoms are strongly pyramidalised [(R)bond angles, 293.7°].…”
Section: Co-oligomers Containing Phosphole Ringsmentioning
confidence: 99%
See 1 more Smart Citation